2019
DOI: 10.3389/fphys.2019.01036
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Fatty Acids and Ketone Bodies Sensing and Role of FAT/CD36 in the Regulation of Food Intake

Abstract: The obesity and type-2 diabetes epidemic is escalating and represents one of the costliest biomedical challenges confronting modern society. Moreover, the increasing consumption of high fat food is often correlated with an increase in body mass index. In people predisposed to be obese or already obese, the impaired ability of the brain to monitor and respond to alterations in fatty acid (FA) metabolism is increasingly recognized as playing a role in the pathophysiological development of these disorders. The br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 182 publications
3
25
1
Order By: Relevance
“…CD36 is a central regulator for cell metabolism, maintaining lipid and glucose metabolism. The protein also transduces signaling to mediate its role in inflammation 33 , lipid metabolism, and insulin responsiveness, contributing to the pathogenesis of metabolic diseases, such as obesity, atherosclerosis, NAFLD, and type 2 diabetes 34 . The function of CD36 in fatty acid metabolism is well documented and several studies have revealed its association with cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD36 is a central regulator for cell metabolism, maintaining lipid and glucose metabolism. The protein also transduces signaling to mediate its role in inflammation 33 , lipid metabolism, and insulin responsiveness, contributing to the pathogenesis of metabolic diseases, such as obesity, atherosclerosis, NAFLD, and type 2 diabetes 34 . The function of CD36 in fatty acid metabolism is well documented and several studies have revealed its association with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The function of CD36 in fatty acid metabolism is well documented and several studies have revealed its association with cancer. CD36-mediated exogenous fatty acid uptake and oxidation leads to cancer growth and metastasis 23 , 34 . Metabolic reprogramming has been recognized as a hallmark of cancer, changes of glucose, fatty acid, and glutathione metabolic pathways are often involved.…”
Section: Discussionmentioning
confidence: 99%
“…Besides glucose and lactate, ketone bodies represent an alternative fuel for neurons during fasting or extended exercise periods, reaching even 60-70% of the total energy supply for the brain [64]. Under low blood glucose levels adipocytes perform ketogenesis, releasing ketone bodies in the form of acetoacetate and b-hydroxybutyrate (BHB) into the bloodstream, which can cross the blood-brain barrier and be imported via MCT2 into neurons [65]. Additionally, unlike neurons, astrocytes are capable to perform ketogenesis providing with ketone bodies to neighbouring neurons [66].…”
Section: Energy Metabolism In the Brainmentioning
confidence: 99%
“…As mentioned above, next to the hormonal regulation of food intake, circulating nutrients [e.g., glucose, fatty acids (FA)] are sensed in the hypothalamus and provide information about the energy state (Matzinger et al, 2000;Lam et al, 2005;Migrenne et al, 2006;Rijnsburger et al, 2016;Le Foll, 2019). More specifically, FA metabolism in the hypothalamus is suggested to function as sensor for nutrient/energy availability integrating both nutritional and hormonal signals.…”
Section: Introductionmentioning
confidence: 99%